The ATF6α arm of the Unfolded Protein Response mediates replicative senescence in human fibroblasts through a COX2/prostaglandin E2 intracrine pathway. (March 2018) - Cormenier, Johanna; Martin, Nathalie; Deslé, Julie; Salazar-Cardozo, Clara; Pourtier, Albin; Abbadie, Corinne; Pluquet, Olivier
Highlights: The ER stress inducer DTT causes premature senescence through ATF6α in NHDFs. COX2 expression and activity are under the regulation of ATF6α during replicative and stress-induced premature senescence in NHDFs. The senescence-associated morphological changes in NHDFs are in part controlled by the ATF6α/COX2 axis. COX2 effect on senescence-associated morphological changes relies on the production of PGE2 which acts intracrinally on EP3 receptors. Abstract: Senescence is recognized as a cellular state acquired in response to various stresses. It occurs in correlation with the activation of the Unfolded Protein Response (UPR) pathway. However, the UPR targets which might relay the establishment of the senescent phenotype are not known. Herein, we investigated whether the up-regulation of the COX2 (PTGS2) limiting enzyme in the prostaglandin biosynthesis pathway, known to mediate cellular senescence in normal human fibroblasts, could be controlled by the UPR sensors ATF6α, IRE1α and PERK. We found that UPR inducers cause premature senescence through an increase in COX2 expression, and an overproduction of prostaglandin E2 (PGE2 ) in wild type fibroblasts but not in ATF6α invalidated ones. In replicative senescent fibroblasts, ATF6α and IRE1α silencing abrogated COX2 up-regulation and PGE2 production. The expanded ER and the large cell size characteristics of senescent fibroblasts were both reduced upon the invalidation of COX2 as well as ATF6α. These effects of the ATF6α invalidation were prevented by favoring the import of PGE2, but not just by supplying extracellular PGE2 . Taken together, our results support a critical role of ATF6α in the establishment and maintenance of cellular senescence in normal human fibroblasts via the up-regulation of a COX2/PGE2 intracrine pathway.